Therapeutic Targeting of Osteopontin in Breast Cancer Cells - Kundu, Gopal C.; Saraswati, Supriya; Sanyal, Megha; Bulbule, Anuradha; Ramdasi, Anuja; Kumar, Dhiraj; Behera, Reeti; Ahmed, Mansoor; Chakraborty, Goutam; Kumar, Vinit; Jain, Shalini; S., Gowrishankar; et al. (IntechOpen, 2011)
None